Implementation of Sustainable Development Goal 12 in Cities: Best Practices - Jastrzębska, Ewa (Studia Ecologiae et Bioethicae, 2022)
Although urban areas do not occupy much of the Earth’s surface, their inhabitants account for more than half of the global population. Moreover, cities consume most of the world’s energy while emitting the bulk of carbon compounds. For that reason, metropolises should seek to implement the concept of sustainable development, as is practically embodied in the 17 Sustainable Development Goals (SDGs). Although SDG 11, addresses cities directly, all the others contain an “urban” aspect, too. One of the SDGs which is rising in importance due to the global problem of over-consumption and, consequently, over-production of waste is SDG 12 concerning responsible production and consumption. The purpose of this article is to present the actions that cities can take to achieve SDG 12. The study is based on a critical analysis of the literature on the subject, as well as on web research and case studies. Attainment of SDG 12 requires the pursuit of the concept of a circular economy (CE), namely, one where the value of products, materials and resources is maintained in the economy for as long as possible, and the generation of waste is minimised. The review of best practices from Polish and other cities, demonstrates their efforts to work towards a CE through diverse and comprehensive initiatives, beyond their tasks and competencies. Moreover, metropolises encourage their stakeholders: (i) entrepreneurs, to join them in following the CE path by creating conditions that are conducive to implementing responsible production; and (ii) residents and city users, by promoting sustainable consumption.